2000
DOI: 10.1590/s0066-782x2000001200003
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange during exercise in different evolutional stages of chronic Chagas' heart disease

Abstract: Objective -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
(25 reference statements)
1
11
0
4
Order By: Relevance
“…The decrease in catalase activity could be related to the increased anaerobic metabolism parallel to the increase in ventricular remodeling. Pedrosa et al [34], and Oliveira et al [35] showed that healthy subjects have better O 2 utilization per unit of body mass compared to late chagasic patients. It is well known that O 2 consumption is almost linear to O 2 U− and H 2 O 2 generation [38][39][40] and, therefore, diminished oxidative metabolism will render lower ROS production.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The decrease in catalase activity could be related to the increased anaerobic metabolism parallel to the increase in ventricular remodeling. Pedrosa et al [34], and Oliveira et al [35] showed that healthy subjects have better O 2 utilization per unit of body mass compared to late chagasic patients. It is well known that O 2 consumption is almost linear to O 2 U− and H 2 O 2 generation [38][39][40] and, therefore, diminished oxidative metabolism will render lower ROS production.…”
Section: Discussionmentioning
confidence: 98%
“…In accordance to [33], group II is characterized by higher intracellular lesions, inflammation and fibrosis compared to groups IA and IB, while in group III there is a greater incidence and greater severity of such abnormalities, indicating a direct correlation between these processes and the degree of cardiac remodeling. The modified Los Andes classification reviewed by Xavier [25] shows that the higher the degree of ventricular remodeling the higher the mortality, and some studies have used this classification for clinical evaluations [15,34,35]. Taken these clinical aspects into consideration, in the present study the patients were ranked according to the modified classification reviewed by Xavier [25], and also because it indicates the extensive cardiac damage in chronic chagasic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the TET, only the tests of patients reaching 7 MET, limit defined as a submaximal exercise level (good correlation between the anaerobic threshold achieved and the 7-MET load achieved), were considered for analysis 11 . Two observers analyzed and compared the ECGs at rest and during exercise (around 7 MET), identifying in both situations the 30-second period with the greatest number of ventricular arrhythmias and/or NSVT episodes.…”
Section: Methodsmentioning
confidence: 99%
“…The functional capacity of patients in the initial phase of chronic Chagas heart disease is higher than those in advanced phases 11. …”
Section: Discussionmentioning
confidence: 92%